The Role of Instagram in Enhancing Student Self-Disclosure: A Mixed-Methods Study on Students at SMA of Palangka Raya - Siti Norhidayah; Nurul Wahdah; Surawan Surawan; Jasiah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Teenagers widely use Instagram to express themselves, including self-disclosure. This study aims to analyze the role of Instagram in encouraging students' self-disclosure and the factors that influence it. Referring to the theory of intensity of social media use, as well as the five dimensions of self-disclosure, this study employed a mixed-methods approach with a sequential explanatory design, involving 111 students from class XI at SMAN 4 Palangka Raya. Quantitative results revealed a positive correlation between Instagram usage intensity and self-disclosure (r = 0.476), accounting for 22.6% of the variance. Qualitatively, four main factors were found: purpose of use, type of content, trust in followers, and perception of privacy. The findings confirm that Instagram can be a positive tool for self-disclosure when used with an emphasis on ethical and privacy awareness. Educators and parents are expected to play an active role in students' digital literacy. Keywords: role, instagram media, self-disclosure, students